Sphenopalatine artery ligation: a brief review - Munjal, Manish; Sandhu, Loveleen; Munjal, Shubham; Nanda, Kshitij; Gupta, Pritish; Binepal, Tegbir Singh; Gupta, Dhruv; Patel, Ayame D.; Arora, Vineeta (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Nasal bleeds, anterior or posterior necessitate varied stepladder interventions like the simple thumb-index finger pinch technique, insertion of spindle cotton plug or the layered roller gauze, the latex urological Sir Foleys catheter and its fine grade silicone modifications, feeding vessel bipolarization or embolization. The middle turbinate being the line of demarcation between the internal and external carotid supply to the nose. The anterior and posterior ethmoid arteries are the distributaries of the internal carotid system. The former is ligated or fulgurated via the external Howarth or the intranasal endoscopic approach. The sphenopalatine artery is the primary distributary of the external carotid system to the nasal and the paranasal region, which is accessed trans-nasally or trans-antrally and ligated, clipped or fulgurated in uncontrolled epistaxis. Endoscopic visualization facilitates the procedure. The intervention is precise, quick and avoids the uncomfortable sequel of conventional nasal tamponade, like excess nasal crusting, anosmia, cacosmia and cheek paraesthesia.